Akta Pengakuan Utang Dengan Jaminan Sebagai Upaya Penyelesaian Wanprestasi Pada Perjanjian Kerjasama - Inayah Alicia Putri; Siti Nurul Intan Sari Dalimunthe (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to analyze the implementation of the agreement after the occurrence of default and application of alternative settlement of cases. In this study the authors used a normative juridical approach, with qualitative data analysis techniques. The results of this study indicate that generally the implementation of the agreement after the debtor is declared in default depends on the claims submitted by the victim, such as demands for cancellation of the agreement, demands for fulfillment of performance, demands for compensation, or a combination of the three types of claims. The parties in this case agreed not to continue the cooperation as they should, and to take alternative settlement steps through non-litigation channels without any claims for compensation in any form. The alternative settlement carried out by the parties in this case is to make a new agreement in the form of a debt acknowledgment deed with a guarantee made before a notary.